Highly oriented CuSbS2 thin films by rapid thermal processing of pre-annealed Sb2S3-Cu layers for PV applications. (1st March 2019) - Vinayakumar, V.; Shaji, S.; Avellaneda, D.A.; Aguilar Martinez, J.A.; Krishnan, B.
Abstract: Copper antimony sulfide (CuSbS2 ) is an emerging absorber material in solar cells due to its nearly ideal optoelectronic properties, earth abundancy and environmentally benign composed elements. In the present work, highly oriented CuSbS2 thin films have been prepared by annealing layered structures of chemical bath deposited Sb2 S3 and thermal evaporated Cu, followed by rapid thermal processing (RTP). A systematic study was performed by varying the processing time. Crystalline structure, morphology, elemental composition, chemical state, optical and electrical properties of the films formed at different conditions were analyzed using various techniques. X-Ray diffraction analysis showed that the post RTP treatment resulted CuSbS2 thin films with preferential orientation along (301) planes perpendicular to the substrate surface, on glass as well as Mo coated glass substrates. Optical properties showed that CuSbS2 has a direct bandgap of 1.6 eV supported by photo-current sensitivity at different wavelengths, which is nearly the ideal bandgap for an absorber layer in solar cell. Graphical abstract: Highlights: CuSbS2 thin films with highly oriented grain growth by RTP of pre-annealed Sb2 S3 -Cu layers on glass and Mo- substrates. Fast crystallization at lower temperature for CuSbS2 on Mo/Glass. Improved photophysical properties for CuSbS2 thin films with oriented grain growth.